Ten-year trends in lipid management among patients after myocardial infarction in South Korea - Oh, Seok; Cho, Kyung Hoon; Kim, Min Chul; Sim, Doo Sun; Hong, Young Joon; Kim, Ju Han; Ahn, Youngkeun; Lee, Sang Yeub; Shin, Min-Ho; Kim, Weon; Jeong, Myung Ho (PloS one, 2024)
Dyslipidemia is an important risk factor for acute myocardial infarction. However, real-world data on its prevalence and lipid management trends for Korean patients with acute myocardial infarction are limited. This study aimed to determine the 10-year temporal trends in dyslipidemia prevalence and lipid management in this patient population. The study used a merged database of two nationwide observational cohorts (2011-2020) that included 26,751 participants. The primary endpoints were the achievement rates of the (1) absolute low-density lipoprotein cholesterol (LDL-C) target of <70 mg/dL (<1.8 mmol/L), (2) relative LDL-C target reduction of >50% from the baseline, (3) absolute or relative LDL-C target (American target), and (4) both absolute and relative LDL-C targets (European target). The dyslipidemia prevalence increased from 11.1% to 17.1%, whereas the statin prescription rate increased from 92.9% to 97.0% from 2011 to 2020. The rate of high-intensity statin use increased from 12.80% in 2012 to 69.30% in 2020. The rate of ezetimibe use increased from 4.50% in 2016 to 22.50% in 2020. The high-intensity statin and ezetimibe prescription rates (0.20% to 9.30% from 2016 to 2020) increased gradually. The absolute and relative LDL-C target achievement rates increased from 41.4% and 20.8% in 2012 to 62.5% and 39.5% in 2019, respectively. The American (45.7% in 2012 to 68.6% in 2019) and European (16.5% in 2012 to 33.8% in 2019) target achievement rates also increased. The adoption of lipid management guidelines in clinical practice has improved. However, continued efforts are needed to reduce the risk of recurrent ischemic events.